Analisa Sistem Informasi Penjualan Kebab Bongout Eat Menggunakan Metode Scrum - Rifa Ruliansyah Nasution; Zulfahmi Syahputra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Kebab is a food from the Middle East. Many kebab sales are carried out by kebab entrepreneurs. Bongout Eat is one shop that sells kebabs online. This shop still uses manual recording in recording the sale of the kebab. Revenue analysis is a difficult thing to do without a sales information system. The author tries to design and build a kebab sales information system at Bongout Eat in order to see the sales results per period. The system can display sales results as of the desired date. Sales can be increased by looking at the results of sales that have already taken place. With this kebab sales information system. Bongout Eat stores will get more benefits in increasing their sales.